Die Vegetationskarte als Ansatzpunkte zu landschaftsökologischen Untersuchungen - Haffner, Willibald (ERDKUNDE, 1968)
Vegetation maps permit comprehensive ecologic statements because of the ecologic indicator value of individual plants and plant communities. In the vegetation map of the middle Nahe Valley, the cartographic methodology has closely followed that of Gaussen. The topographic base is presented in its entirety, the colours were chosen after Gaussen, but adapted to local conditions e. g. blue for carr on damp sites, green for woodland, red for xero therm sites and plant communities; all land use such as arable or hay meadow is coloured yellow. Intensive cultures (vineyards) are presented in light violet. The accompanying combined vegetation and soil-type profile underlines the dependence of ecology on topographic conditions. A glance at the small map of floral geography and at the vegetation and climate profile of the Saar-Hunsruck-Nahe area shows that, on the map area under investigation, the Nahe Valley is very dry and warm for central European conditions and is extremely rich in sub-mediterranean and pontic floral elements. The 1:50 000 scale underpinning the vegetation map re quires that the units mapped should correspond to topo graphic vegetation complexes which, following the catena principle, disaggregate into a chain of edaphically-conditioned variants. The interpretation of the vegetation map with its ac companying smaller maps aims, through progressive comparison of the relationships between elements recognised in the individual analytic maps and other ecologic phenomena, to attain an increasingly complex picture of ecologic processes so that in the end a simplified model-like idea of operational events and changes within the eco system of the mapped area of the Nahe Valley and its constituent areas can be gained.